Pheochromocytoma and pregnancy with abruptio placenta - Korichi, Noureddine; Shaikh, Nissar; Mathew, Gisha; Alloub, Mahommad Amin; Boursaly, Ibrahim; Scott, Nick (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
A 41 year old previously healthy woman (Gravida 4, para 3) was presented to our hospital at 29 weeks gestation, with bleeding Per Vagina (PV) and severe hypertension (190/100). She underwent a routine obstetric examination at 12 weeks gestation and since then she has not undergone any antenatal follow-up. She developed episodes of severe headache, dizziness, sweating, and nausea. She visited a private hospital and was noted to be severely hypertensive (190/120) with headache and palpitations. An ultrasound abdomen was done which showed left suprarenal mass, and a diagnosis of pheochromocytoma was made. She was treated there with antihypertensive medications. When Blood pressure got controlled, she was discharged against medical advice. At 29 weeks, she suddenly developed severe headache and bleeding PV. She visited our centre and was diagnosed to have abruptio- placenta with foetal distress. An emergency caesarean section was done, and following which the patient was treated in the ICU with antihypertensive under invasive monitoring. An MRI demonstrated a left pheochromocytoma. A laparoscopic adrenelectomy was planned later and she got discharged on antihypertensive following an uneventful period of recovery. She got operated later in her country. A laparoscopic left adrenelectomy was done. She is off all medications now and is currently asymptomatic.